A novel trench fibre push-out method to evaluate interfacial failure in long fibre composites - De Meyere, RMG; Song, K; Gale, L; Harris, S; Edmonds, IM; Marrow, TJ; Saiz, E; Giuliani, F; Armstrong, DEJ; Gavalda-Diaz, O (Springer, 2021)
Traditional fibre push-outs for the evaluation of interfacial properties in long fibre ceramic matrix composites present their limitations—solutions for which are addressed in this work by introducing the novel trench push-out test. The trench push-out makes use of a FIB milling system and an SEM in-situ nanoindenter to probe a fibre pushed into a trench underneath, allowing in-situ observations to be directly correlated with micromechanical events. SiCf/BN/SiC composites—candidate material for turbine engines—were used as model materials in this work. Different fibre types (Hi-Nicalon and Tyranno type SA3) were coated with BN interphases, presenting mean interfacial shear stresses of 14 ± 7 MPa and 20 ± 2 MPa, respectively, during fibre sliding. The micromechanical technique enabled visualisation of how defects in the interphase (voids, inclusions & milled notches) or in the fibre (surface asperities, non-uniform coatings) affected the variability of interfacial property measurement.